PEMANFAATAN BABADOTAN (Ageratum conyzoides L) UNTUK MENGENDALIKAN HAMA KUTU DAUN PADA TANAMAN CABAI RAWIT (Capsicum frustescent L.) - Indra Wijaya; Saripah Ulpah; Mardaleni (DINAMIKA PERTANIAN, 2018)
ABSTRACT The purpose of this study was to determine the use of Ageratum by planting among the main plants of cayenne pepper as an effort to control aphids. The design used in this study is the One-way Anova Design (one-lane design), which is planting Ageratum on a chili plant plot combined with ageratum with various densities consisting of 7 experimental treatments, namely: A = Without Ageratum., B = Two clumps / plot, C = Four clumps / plot, D = Six clumps / plot, E = Eight clumps / plot, F = Ten clumps / plot, G = Twelve clumps / plot. Each experimental unit contained 4 chili plants and 2 plants were sampled, making a total of 112 plants and a total of 336 Ageratum plants. The results showed that the planting of Ageratum conyzoides influenced plant height, flowering age, harvest age and fruit weight per plant. The best treatment results in treatments without planting Ageratum (A).The aphids population decreases with the increasing population of Ageratum per plot. planting Ageratum affects the number of pests of each species and the percentage of cayenne pepper affected by the virus is getting lower with increasing population Ageratum per plot. The treatment of Ageratum plants on cayenne pepper plants can control pests and diseases but reduce production. Keywords: Babadotan, Aphids, Cayenne pepper